PUBLIC DIPLOMACY AND POLITICAL COMMUNICATION STRATEGIES IN NATION BRANDING - Ahmad Sampurna Rambe; Afdal Hafiz Taka; Atika Syalsabila Putri; Fauzul Azmi Daulay; Rizky Adi Candra Nasution (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2025)
In the era of globalization, characterized by narrative competition among nations and the rapid flow of digital information, a country's image has become a strategic asset that determines legitimacy and influence on the international stage. This study aims to analyze the relationship between public diplomacy and political communication strategies in shaping Indonesia’s national image. Using a qualitative-descriptive approach and literature review method, this research examines various case studies, policy documents, and academic literature to understand the patterns and practices of strategic communication employed by both state and non-state actors. The findings indicate that Indonesia's public diplomacy is implemented through various approaches, including digital campaigns, cultural exchanges, and the use of social media by political figures and government institutions. Structurally designed political communication strategies through national narratives, cultural symbols, and political representation have succeeded in building public trust and strengthening national identity in the eyes of the international community. Cultural approaches and digital communication serve as key tools in fostering emotional closeness and two-way interaction with the global public. These findings reinforce the importance of integrating public diplomacy and political communication as a foundation for building a positive, competitive, and sustainable national image.